O relacionamento entre alunos e IES: a reputação, a satisfação e a lealdade em tempos de covid-19 - Brandão, Cláudio de Oliveira (2022)
In Brazil, with the increase in the number of people infected by Covid-19, social isolation was adopted and influenced the economy, loss of jobs and closing of companies. With social distancing in March 2020, face-to-face classes were suspended to avoid agglomeration and, many institutions, chose to adopt remote classes. This option influenced the way educational institutions related to their students, as the direct and personal contact was broken. This study presents models and scales designed with the intention of measuring the relationship and loyalty between companies and customers. Loyalty can be defined as willingness through a consumer's attachment to a particular brand and their intention to consistently buy again in the future. Relationship research addresses the importance of two antecedent attributes of loyalty: satisfaction and reputation. The objective is to understand how the relationship adopted during the pandemic period influenced the loyalty of students to their HEIs in the Center-West region, still little explored, particularly in the context of Covid-19. The methodological approach was quantitative descriptive, survey, through a single cross-sectional study. The sampling is intentional non-probabilistic and the questionnaire is applied to students enrolled in private educational institutions in the Midwest region. The data analysis used was through descriptive and inductive statistics, in addition to a structural equation model. The results confirm the importance of satisfaction and reputation in relation to loyalty and reputation satisfaction during the pandemic period. From the antecedents adopted in the model, social activities and information technology can be highlighted with relevant direct effects on loyalty and, possibly impacted by the context of the pandemic. The study also demonstrated the influence of the identifying variables age range, family income and academic term of students on the perception of loyalty. The main contribution in practical and managerial aspects is the confirmation that under certain environments and contexts students' perception of loyalty towards their educational institution can be significantly modified, inverting the weight of importance of certain attributes on it. The results confirm the importance of managing the relationship adopted by HEIs with their students as essential for their retention.